Learning D3.js 4 Mapping - Newton, Thomas (Packt Publishing, 2017)
Crisp and concise guide on building impressive maps as well as visualizations with D3 a JavaScript library About This Book Dive into D3.js and apply its powerful data binding ability in order to create stunning visualizations Learn the key concepts of SVG, JavaScript, CSS and the DOM to bring data and shapes to live in the browser Solve common problems faced while building interactive maps Acquire key web development skills from the creating your interactive to testing and finally publishing it. Who This Book Is For This book is for people with at least a basic knowledge of of web development (basic HTML/CSS/JavaScript). You don't need to have worked with D3.js before. What You Will Learn Work with SVG geometric shapes Learn to manage map data and plot it with D3.js Add interactivity and points of interest to your maps Compress and manipulate geoJSON files with the use of topoJSON Learn how to write testable D3.js visualizations Build a globe with D3.js and Canvas and add interactivity to it. Create a hexbin map with D3.js In Detail D3.js is a visualization library used for the creation and control of dynamic and interactive graphical forms. It is a library used to manipulate HTML and SVG documents as well as the Canvas element based on data. Using D3.js, developers can create interactive maps for the web, that look and feel beautiful. This book will show you how build and design maps with D3.js and gives you great insight into projections, colors, and the most appropriate types of map. The book begins by helping you set up all the tools necessary to build visualizations and maps. Then it covers obtaining geographic data, modifying it to your specific needs, visualizing it with augmented data using D3.js. It will further show you how to draw and map with the Canvas API and how to publish your visualization. By the end of this book, you'll be creating maps like the election maps and the kind of infographics you'll find on sites like the New York Times. Style and approach This step by step guide with pragmatic examples will help you create maps and amazing visualizations. Downloading the example code for this book. You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the code file.